Unveiling malignancy patterns among rheumatology patients: Insights from a retrospective study - Senem Tekeoğlu (Ulusal Romatoloji Dergisi)
Objective: Malignancy is a significant comorbidity in patients with rheumatic diseases. This study investigates the incidence, prevalence, and risk factors of malignancies among patients with rheumatic diseases and non-inflammatory conditions in a rheumatology clinic. Methods: A retrospective analysis was conducted on 2,600 patients between January 2021 and January 2024. Data collected included patient demographics, rheumatic disease types, non-inflammatory conditions, treatments, and cancer history. Statistical analyses included chi-square tests, Fisher’s exact tests, Mann-Whitney U tests, logistic regression, and standard incidence ratio (SIR) calculations. Results: Of the 2,600 patients, 100 had a cancer history, with a median age of 66 years, higher than those without cancer (p<0.001). Breast cancer was the most common malignancy (29%), followed by gynecologic and respiratory cancers. Cancer prevalence was higher among rheumatoid arthritis (RA) and osteoarthritis patients and lower in ankylosing spondylitis and fibromyalgia patients. Twenty-six patients received a cancer diagnosis after the onset of a rheumatic or non-inflammatory condition. In female patients, gynecologic cancers [SIR=3.76, 95% confidence interval (CI)=1.2-8.7, p=0.005] and lymphoma (SIR=8.14, CI=1.6-23.7, p=0.001) were more common. In male patients, the total number of cancers was significantly higher (SIR=381, CI=182.7-700.8, p<0.001). Moreover, two patients treated with nivolumab developed new-onset RA and psoriatic arthritis, while one patient treated with ribociclib developed systemic sclerosis. Logistic regression identified age [odds ratio (OR)=1.03], male gender (OR=2.16), the presence of inflammatory diseases (OR=4.52), and Charlson Comorbidity index score (OR=5.65) as significant predictors of cancer diagnosis. Conclusion: This study highlights the need for vigilant cancer screening in rheumatic disease patients, especially the elderly. Future research should focus on prospective studies to develop targeted cancer prevention and management strategies for this population.